THE ROLE OF THE EUROPEAN BANK FOR RECONSTRUCTION AND DEVELOPMENT IN PROMOTING AND FINANCING RENEWABLE ENERGY PROJECTS (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
Abstract:The countries of the European Union, unlike the Republic of North Macedonia andthe countries of Southeastern Europe, invest heavily in increasing the share of renewableenergy sources in total energy production, hence becoming world leaders in the productionof “clean” electricity. Therefore, the European Bank for Reconstruction and Developmentaims to provide support to the economy and households in the Republic of North Macedoniathrough loans and grants to increase the share of renewable energy sources, especially solarenergy, reduce dependence on electricity imports, as well as reducing coal energy production.The Energy Strategy of the Republic of North Macedonia until 2040 defines the long-termgoals for the development of individual energy activities in order to ensure security in thesupply of different types of energy, while providing conditions and ways for environmentalprotection and measures for realization of protection. The strategy relies on green growth andoffers solutions to tackle climate change, especially in the green scenario. The green scenarioenvisages achieving the share of renewable energy sources up to 44% in 2040 in the total finalenergy consumption. The role of the European Bank for Reconstruction and Developmentin the promotion of renewable energy sources is indisputable, as well as achieving the goalsof the Energy Strategy and the green scenario, and the ultimate goal is nature protection andgreater energy efficiency.